EFEKTIVITAS PROGRAM FAMILY CORNER BERBASIS MASJID DALAM MEMBANGUN KETAHANAN KELUARGA: ANALISIS TEORI EFEKTIVITAS HUKUM SOERJONO SOEKANTO - Abdur Rohman Baihaqy; Burhanuddin Susamto; Miftahul Huda (LPPM STAI Muhammadiyah Probolinggo, 2026)
The high divorce rate in Malang City, which reached 1,706 cases in 2024, has also triggered an increase in broken homes and disrupted children's socio-psychological development. To address these issues, the Family Corner Program is offered as a mosque-based family consultation, education, and mentoring service. This study aims to analyze the program's effectiveness in strengthening family resilience using Soerjono Soekanto's theory of legal effectiveness. The method used is empirical legal research with a sociological approach through observation, interviews, and documentation studies, and analyzed using the Miles and Huberman model. The results indicate that Family Corner is quite socially effective through the synergy between the Ministry of Religious Affairs, DMI, UIN Malang, and the local government, and has received a positive response from the community. This program increases family awareness of the importance of communication, harmony, and religious values. However, its effectiveness is not optimal due to limitations in the legal basis, human resources, facilities, funding, and the community's culture of shame in consulting. Based on Soekanto's five factors of legal effectiveness, this program is categorized as moderate. Regulatory strengthening, capacity building for implementers, and ongoing outreach are needed to make the program more professional and sustainable.